Analisis Perbandingan Penjualan Offline dan Online Produk Fashion Meccanism Sebagai Cara Menarik Konsumen - Lindiawatie, Lindiawatie; Shahreza, Dhona; Wati, Lisna (Pusat Riset dan Inovasi Nasional, 2024)
E-commerce is the main driver of the digital economy in Indonesia at 77%. The 2020-2022 Covid-19 pandemic is increasingly encouraging changes in consumer behavior from direct stores to online. This research was carried out to determine the comparison of offline and online Meccanism fashion sales as an effort to attract consumers. The method is descriptive statistics and the Run Wald Wolfowitz comparison test. The result is that there are significant differences in fashion Meccanism's online and offline sales methods as an effort to attract consumers. Average offline sales are greater than online sales. This means that consumer preferences prefer offline purchases compared to online for fashion Meccanism. However, both methods are equally important to attract consumers. Suggestions for business actors to implement a mix of offline and online sales strategies as an effort to attract consumers and increase sales. The way to do this is by understanding consumer behavior online and offline in shopping.